NET Confusion - Malachowa, Natalia; Kobayashi, Scott D.; Quinn, Mark T.; DeLeo, Frank R. (Frontiers in Immunology, 2016)
Neutrophils are arguably the most important white blood cell for defense against bacterial and fungal infections. These leukocytes are produced in high numbers on a daily basis in humans and are recruited rapidly to injured/infected tissues. Phagocytosis and subsequent intraphagosomal killing and digestion of microbes has historically been the accepted means by which neutrophils carry out their role in innate host defense. Indeed, neutrophils contain and produce numerous cytotoxic molecules, including antimicrobial peptides, proteases, and reactive oxygen species, that are highly effective at killing the vast majority of ingested microbes. On the other hand, it is these characteristics—high numbers and toxicity—that endow neutrophils with the potential to injure and destroy host tissues. This potential is borne out by many inflammatory processes and diseases. Therefore, it is not surprising that host mechanisms exist to control virtually all steps in the neutrophil activation process, and to prevent unintended neutrophil activation and/or lysis during the resolution of inflammatory responses or during steady-state turnover. The notion that neutrophil extracellular traps (NETs) form by cytolysis as a standard host defense mechanism seems inconsistent with these aforementioned neutrophil “containment” processes. It is with this caveat in mind that we provide perspective on the role of NETs in human host defense and disease.